THE RELATIONSHIP BETWEEN TREATMENT ADHERENCE AND KNOWLEDGE WITH THE RECOVERY LEVEL OF TUBERCULOSIS PATIENTS AT LAWAWOI PUBLIC HEALTH CENTER SIDENRENG RAPPANG REGENCY - Suarni; Pratiwi Ramlan; Mardhatillah; Khaeriyah Adri (CV. Fahr Publishing, 2026)
Tuberculosis (TB), an infection produced by Mycobacterium tuberculosis, continues to pose a substantial public health concern. The World Health Organization estimated that 10.7 million individuals developed TB globally in 2024, and Indonesia remained among the countries carrying the greatest disease burden. At primary-care facilities, the proportion of patients who recover has also not consistently met the national minimum standard of 90%. This research examined whether treatment adherence and patient knowledge were related to the recovery level of TB patients at Lawawoi Public Health Center in Sidenreng Rappang Regency. A quantitative, observational-analytic study with a cross-sectional design was applied. The study population included 115 patients listed in the center's TB register, from whom 89 respondents were selected by simple random sampling. Information was gathered through observation, structured questionnaires, and document review, then tested with chi-square analysis at a 0.05 significance level. Treatment adherence was significantly associated with recovery (p = 0.033), whereas knowledge showed no significant association (p = 0.108). The results suggest that consistently completing therapy is a central behavioral element of TB recovery, while knowledge by itself is inadequate when it is not followed by sustained treatment practices and supporting systems. Ongoing counseling, participation of family members, supervision of therapy, and regular patient monitoring are therefore required to reinforce adherence and optimize treatment success. In this context, recovery was treated as the principal outcome of the complete course of care, rather than as a consequence of knowledge alone. The analysis therefore distinguished what patients knew from what they consistently practiced throughout treatment.